Synthesis and characterization of high dielectric constant material based on Er-doped BaTiO3 for capacitor applications - Fatin Adila Ismail author (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2018)
The project scope was to study the solid solution limit of Er- doped BaTiO3. The pure BaTiO3will be prepared as a standard sample and followed by analogues composition of Ba1-xErxTiO3 (x=0, 0.0025, 0.005, 0.0075, 0.01). The properties such as physical properties and structural properties will be studied using XRD and Rietveld Refinement analysis. The electrical properties will be studied using Impedance analyser followed by microstructural properties by using SEM. The composition with the highest dielectric constant will be reported as the main finding for this project.